Experimental Confirmation of an Improved Neutron Dosimeter Using Superheated Liquid Drops - Yeon, Bong Kil (Kansas State University, 1991)
The neutron has made a revolutionary impact both directly and indirectly on science and technology since its discovery by Chadwick1 in 1932. Neutrons are mainly from nuclear reactors, particle accelerator facilities, and isotopic sources such as 252Cf and Pu(Be )3 • The applications of neutrons include power generation, fundamental research on material properties, cancer therapies, and industrial imaging. Neutrons have been recognized as a high-LET radiation of which per unit absorbed dose is more effective then that of the low-LET radiations (e.g. f3 and y rays) are in causing biological damage (e.g. cancer) to human. The increasing use of neutrons thus has raised great concern about the cancer risks that workers and general publics are subjected to. The biological effects caused by neutrons have been studied quite extensively in the past few decades, and much has been ]earned. Despite the wide use of neutrons and the increased human health concern, and in contrary to the increased knowledge about the biological effects due to neutrons, the techniques used to monitor human exposure to neutrons are still quite primitive and inaccurate.